Thermodynamic descriptions of the Ag-X (X = S, As, Lu) systems. (September 2018) - Shi, Chenying; Du, Yong; Hu, Biao; Yang, Biaobiao; Pan, Yafei; Guo, Fangyu; Liu, Shuhong; Du, Qiang
Abstract: Based on the critical evaluation of experimental data available in the literature, for the first time the Ag-X (X = S, As, Lu) binary systems were assessed thermodynamically using the CALPHAD (CALculation of PHAse Diagram) method. The solution phases including liquid, (Ag), (αS), (βS), (αAs), (εAs) and (Lu) were described by the substitutional solution model, and their excess Gibbs energies were described with the Redlich-Kister polynomial equation. In view of the possible existence of associate species Ag2 S and the difficulty to describe the liquid phase by the substitutional solution model, an associate model was used to describe the liquid phase in the Ag-S system. The intermetallic compounds, i.e. αAg2 S, AgLu, Ag2 Lu and Ag4 Lu, were all modeled as stoichiometric compounds. And the intermetallic compounds βAg2 S and γAg2 S were described by two-sublattice model (Ag, S )2 S1 in view of the solubilities. Self-consistent thermodynamic parameters to describe the Gibbs energies of phases in the Ag-S, Ag-As and Ag-Lu systems were obtained. The calculated results were in good agreement with the reported phase equilibria and thermodynamic properties. Highlights: The experimental data available in literature are critically evaluated. An associated model is used to describe the liquid phase in the Ag-S system. The activities of S in liquid Ag-S alloys have been thermodynamically described. The phase diagrams of the Ag-X (X =  S, As, Lu) systems are calculated.